1974
DOI: 10.1021/j100606a001
|View full text |Cite
|
Sign up to set email alerts
|

Homoallylic isomerization of 1-penten-4-yl and the critical energy for methyl + 1,3-butadiene

Abstract: The homoallylic radicals, l-penten-4-yl and 3-methyl-l-buten-4-yl, were generated in the gas phase by adding H to 1,4-pentadiene. Evidence is given that they are in equilibrium even when thermalized at 0°, and that the isomerization critical energy is less than 15 kcal/mol. The decomposition of 3-methyl-lbuten-4-yl to 1,3-butadiene was studied, and a critical energy of 12 ± 1 kcal/mol for the addition of methyl to the 2 position of 1,3-butadiene was obtained. This is around 3 to 4 kcal/mol higher than the usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…1-Penten-4-yl. The chemically activated decomposition of the 1-penten-4-yl radical was studied by Carter and Tardy 19 from experiments on the addition of hydrogen atoms to 1,4-pentadiene. The most interesting observation is the occurrence of a very fast isomerization process, the homoallylic rearrangement, at room temperature.…”
Section: Basis For Estimatesmentioning
confidence: 99%
“…1-Penten-4-yl. The chemically activated decomposition of the 1-penten-4-yl radical was studied by Carter and Tardy 19 from experiments on the addition of hydrogen atoms to 1,4-pentadiene. The most interesting observation is the occurrence of a very fast isomerization process, the homoallylic rearrangement, at room temperature.…”
Section: Basis For Estimatesmentioning
confidence: 99%
“…A polymer has been found to deposit onto the walls of the reaction vessel. Methane and 3-methyl-1-butene are formed in reactions of 1-penten-4-yl radical studied extensively by Carter and Tardy [9]. Methane is presumably accompanied by the equivalent amounts of 1,3-butadiene but this particular hydrocarbon is removed from our system in the effective reaction with SH radicals [lll.…”
Section: (3)mentioning
confidence: 99%
“…The treatment is similar to that for the heptyl radicals, except that the isomerization possibilities are much decreased. We have found that the literature data for the reverse radical addition reaction to dienes (Kerr & Parsonage, 1972) as well as chemical activation results ( Carter and Tardy, 1974) on the addition of hydrogen atom to pentadienes particularly useful in providing a fixed point for estimation. There are however similar problems regarding the presentation of results under conditions where rate constants are no longer constant.…”
Section: Pah and Sootmentioning
confidence: 99%